Dental Anxiety as a Potential Bottleneck in Oral-Systemic Health Pathways: A Conceptual Mapping Review of Review Articles - Kajita, Mika; Pohjola, Vesa; Humphris, Gerald; Lahti, Satu (MDPI AG, 2026)
Background/Objectives:
Although many studies have examined the determinants and management of dental anxiety (DA), its broader placement as a potential bottleneck along oral–systemic health pathways, from the determinants of DA to consequences through dental avoidance, oral outcomes, psychosocial impacts, and possible systemic health outcomes, has not been mapped across the review literature. This review aimed to conceptually map how existing DA reviews are distributed across this pathway, whether this broad framing changed across 5-year periods, and how systemic health outcomes were framed.
Methods:
We conducted a conceptual mapping review of DA-focused review articles published between 2005 and 2025. PubMed and Scopus were searched for English-language narrative, systematic, scoping and umbrella reviews and meta-analyses addressing the determinants or consequences of DA. One reviewer screened records, extracted review characteristics, and classified each review into predefined domains using binary framed/not framed coding rules. A structured AI-assisted prompt was used only to support full-text evaluation across domains; all final coding decisions were made by the reviewer.
Results:
The search identified 851 records; after removing 426 duplicates, 425 unique records were screened, and 39 reviews met the inclusion criteria. Framing concentrated on environmental and psychological determinants and on the pathway from DA to avoidance and poor oral health, whereas broader consequences, including shame, OHRQoL, and systemic health outcomes, were less consistently framed. Across 5-year periods, the broad pattern of framing remained relatively stable. Systemic health outcomes were framed in only a minority of reviews.
Conclusions:
Future research should test hypothesized pathways from DA to broader health consequences using clearly specified bridge mechanisms and appropriate temporal designs.